2022
DOI: 10.1093/pnasnexus/pgac050
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species metabolomic analysis of tau- and DDT-related toxicity

Abstract: Exposure to the pesticide dichlorodiphenyltrichloroethane (DDT) has been associated with increased risk of Alzheimer's disease (AD), a disease also associated with hyperphosphorylated tau (p-tau) protein aggregation. We investigated whether exposure to DDT can exacerbate tau protein toxicity in C. elegans using a transgenic strain that expresses human tau protein prone to aggregation by measuring changes in size, swim behavior, respiration, lifespan, learning, and metabolism. In addition, we examined the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 135 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…Increased oxidative stress over-activates GSK-3β, thereby making tau protein more vulnerable to formation of aggregates and new neurofibrils[ 41 ]. Results from multiple studies indicate that exposure to pesticides modifies the mechanisms involved in tau phosphorylation[ 32 - 34 , 42 , 43 ] (Figure 1 ).…”
Section: Pesticides and Their Impacts On Tau Proteinmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased oxidative stress over-activates GSK-3β, thereby making tau protein more vulnerable to formation of aggregates and new neurofibrils[ 41 ]. Results from multiple studies indicate that exposure to pesticides modifies the mechanisms involved in tau phosphorylation[ 32 - 34 , 42 , 43 ] (Figure 1 ).…”
Section: Pesticides and Their Impacts On Tau Proteinmentioning
confidence: 99%
“…Table 1 shows 7 studies in which the effect of OCs on tau protein phosphorylation was determined[ 42 , 44 - 49 ]. Two clinical studies reported that exposure to these pesticides may be associated with polymorphisms in MAPT and microtubule associated protein 1B gene which are related to the formation of tau aggregates[ 44 , 45 ].…”
Section: Pesticides and Their Impacts On Tau Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…While the C. elegans simple body plan lacks multiple organs present in mammals, many aspects of neuronal development and function are conserved from worms to humans (Bargmann, 1998; Boyd et al, 2010; Vidal‐Gadea & Pierce‐Shimomura, 2012). Mammalian neurotoxins have been shown to alter C. elegans locomotor activity levels and/or behavior patterns (Cole et al, 2004; Gentry et al, 2013; Ju et al, 2014; Kalia et al, 2022; Silva, 2020; Williams & Dusenbery, 1990). Additionally, C. elegans has a high true prediction rate with respect to the effects of human neurotoxicants on behavior (Masjosthusmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%